Mathematical Model and Simulation for the Mechanism of Glucose Uptake in the Cells - Ari Kusumastuti; Mohammad Isa Irawan; Kistosil Fahim (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2025)
Understanding the mechanism of Glucose Transporter 4 (GLUT4) translocation to the cell membrane is essential for describing daily glucose uptake. A normal mechanism maintains glucose homeostasis and reduces the occurrence of Type 2 Diabetes Mellitus (T2DM) and its complications. Kinetic reactions are crucial for revealing the interactions involving proteins, enzymes, and complexes within the system. We propose a system of ordinary differential equations (ODEs) to elucidate the underlying mechanism under the assumption of non-conservative complexes . The insulin signaling pathway, which includes the GLUT4 mechanism, serves as the basis for reconstructing the necessary kinetic reactions. Investigating the behaviour of the model through numerical simulations and dynamics within parameters and initial conditions from relevant researchs .